2008
DOI: 10.1007/s00198-008-0768-y
|View full text |Cite
|
Sign up to set email alerts
|

Women and men with hip fractures have a longer femoral neck moment arm and greater impact load in a sideways fall

Abstract: A longer moment arm in the sideways fall increases the resultant force applied to the hip predisposing to hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 31 publications
(33 reference statements)
0
21
0
Order By: Relevance
“…Therefore, both the direct effect of sex steroid deficiency and the indirect effect of the decrease in motor activity appear to contribute to increases in FNAL following ovariectomy. Greater FNAL has been associated with increased risk of fracture independently of age, height, weight, and bone mineral density, which might be related to the fact that a lower force is needed to produce a fracture when the femoral neck moment arm is longer [32]. Notably it has also been suggested that some of the alterations in bone geometry observed following menopause represent compensatory adaptations to counteract the deterioration of bone tissue properties [33].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, both the direct effect of sex steroid deficiency and the indirect effect of the decrease in motor activity appear to contribute to increases in FNAL following ovariectomy. Greater FNAL has been associated with increased risk of fracture independently of age, height, weight, and bone mineral density, which might be related to the fact that a lower force is needed to produce a fracture when the femoral neck moment arm is longer [32]. Notably it has also been suggested that some of the alterations in bone geometry observed following menopause represent compensatory adaptations to counteract the deterioration of bone tissue properties [33].…”
Section: Discussionmentioning
confidence: 97%
“…In fact, from a biomechanical point of view, the wider the NSA and the longer the HAL, the greater the force absorbed by the proximal femur when falling on the lateral side [26], because of a longer moment arm. Nevertheless, this explanation of the relationship between DXA-measured PFG parameters and hip fracture risk has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…This follows the biomechanical concept that the wider the femoral NSA the higher the bending moment at the FN and the higher the impact force imposed on the FN, which results in a greater probability of fracture. 19,21,27,28 Therefore, the ability of NSA to predict hip fracture in males independent of BMD was examined. It was found not only that FN-BMD was the best hip fracture predictor in males but also that NSA does not predict hip fracture independent of FN-BMD.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 This evidence, however, mainly derives from studies carried out in females, 9-13 whereas contradictory results characterize studies carried out in males. [14][15][16][17][18][19][20] Authors' opinions seem to vary widely about the ability of the neck shaft angle (NSA), one of the PFG factors, to predict osteoporotic hip fractures in males, [14][15][16]21 whereas its association with the risk of hip fracture in females 10,11,14,22 is generally accepted. Gender differences in the hip anatomy 23 have been put forward as a possible explanation for the different relationship of NSA with the hip-fracture risk between genders, whereas geographic and racial differences 24 among the examined male populations have been advocated as a possible cause of authors' discrepancies on the relationship between NSA and the hip-fracture risk in males.…”
Section: Advances In Knowledgementioning
confidence: 99%